Optimasi Efisiensi Pengisian Baterai pada Sepeda Statis Berbasis Arduino menggunakan Algoritma Particle Swarm Optimization (PSO) - Nevlin Ferdinand Suharya Wangga; Efendi S Wirateruna; Angguh Prastoko (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study develops a battery-charging system for a stationary bicycle as an alternative renewable micro-energy solution by converting the user’s pedaling motion into electrical power. The primary objective is to enhance charging efficiency through the implementation of the Particle Swarm Optimization (PSO) algorithm to regulate the PWM signal generated by an Arduino-based controller. The research method includes mechanical and electronic design, integration of current and voltage sensors, implementation of a buck-boost converter, development of the PSO algorithm, and performance testing of the prototype. System evaluation was carried out by comparing the performance before and after applying PSO using parameters such as voltage, current, output power, efficiency, and MAPE error. The results show a significant improvement, including a 36.5% increase in output power, efficiency improvement from 23% to 31.5%, and a reduction in MAPE error from 9.4% to 4.1%. The PSO algorithm effectively adjusts the PWM duty cycle in response to variations in load and generator speed, resulting in a more stable, adaptive, and efficient charging process.